Accumulation of PBDEs and MeO-PBDEs in notothenioid fish from the South Shetland Islands, Antarctica: An interspecies comparative study. (July 2021) - Ríos, Juan Manuel; Mammana, Sabrina B.; Moreira, Eugenia; Poma, Giulia; Malarvannan, Govindan; Barrera-Oro, Esteban; Covaci, Adrian; Ciocco, Nestor F.; Altamirano, Jorgelina C.
Abstract: Concentrations of polybrominated diphenyl ethers (PBDEs) and methoxylated polybrominated diphenyl ethers (MeO-PBDEs); are reported in specimens of fish notothenioids Chaenocephalus aceratus (SSI), Trematomus bernacchii (ERN), and Nototheniops nudifrons (NOD) from the South Shetland Islands, Antarctica. Significant differences in the accumulation of 2′-MeO-BDE-68 and 6-MeO-BDE-47 were detected among the analysed species. MeO-BDEs were significantly higher in SSI (11.7, 8.6, and 14.1 ng g −1 lw) than in NOD (1.63, 1.63, and 3.0 ng g −1 lw) in muscle, liver, and gill, respectively. Feeding ecology traits explain the accumulation patterns of MeO-PBDEs. SSI has a higher feeding activity with a broader diet, followed by ERN, whereas NOD is a benthic/sedentary fish with a narrower diet. The accumulation of PBDEs was neither species-, nor tissue-specific. The current study expands the knowledge concerning the accumulation of PBDEs and MeO-PBDEs in Antarctic marine fish and supports the importance of species-specificity in the accumulation of MeO-PBDEs. Graphical abstract: Unlabelled Image Highlights: Marked interspecific differences for notothenioid fish in MeO-PBDE accumulation BDE-47 and 6-MeO-BDE-47 contributed 53 and 90% to the total load, respectively. C. aceratus and N. nudifrons showed the highest and lowest MeO-PBDE levels, respectively. C. aceratus and N. nudifrons had a broader and narrower diet, respectively.